EFFECT OF WORKING CAPITAL TURNOVER, RECEIVABLE TURNOVER AND FIRM SIZE ON PROFITABILITY WITH LIQUIDITY AS A MEDIATION VARIABLE AT PT. RAHMA FURNITURE AND PT. CAKRAWANA FURNINDO SEMARANG 2016-2020 PERIOD - Patricia Dhiana Paramita; Arditya Dian Andika (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
In principle, the profitability of a company is influenced by working capital turnover, receivable turnover and firm size. An analysis of working capital turnover, receivable turnover and firm size for each company is very important to know the current financial condition of the company and the financial situation in the future. This study aims to determine the effect of working capital turnover, receivable turnover and firm size partially on profitability mediated by liquidity. Sources of data used are secondary data, which relate to the object of research, namely PT. Rahma Furniture and CakrawanaFurnindo Semarang, a company engaged in the furniture sector, in the form of financial data from 2016 to 2020. The analysis technique used is multiple linear regression, path analysis, classical assumption test and goodness of fit test. The calculation results show that working capital turnover, receivable turnover and firm size partially have a positive and significant effect on liquidity and profitability and liquidity has a positive and significant effect on profitability. In addition, liquidity does not mediate the effect of working capital turnover on profitability, but liquidity partially mediates the effect of receivable turnover and firm size on profitability. Policies that need to be carried out by management are improving the management of working capital turnover, receivable turnover and firm size, in order to increase company profitability.